EFEKTIVITAS PEMBERIAN JUS BAYAM HIJAU TERHADAP PENINGKATKAN KADAR HEMOGLOBIN PADA IBU HAMIL - Yeki (Politeknik Tiara Bunda, 2025)
The problem of anemia in pregnancy increases the risk of postpartum hemorrhage, which can contribute to higher maternal mortality rates (Dai, 2021). MMR is one of the global SDGs targets, which aims to reduce MMR to 70 per 100,000 live births by 2030 (Bappenas, 2021). Based on the 2019 Riskesdas results, it was shown that 48.9% of pregnant women in Indonesia experienced anemia (Batmomolin, et al., 2024). The purpose of this study was to determine the effectiveness of green spinach juice administration on increasing hemoglobin levels in third trimester pregnant women at Clinic GM Waras Bengkulu Utara. This research used a quantitative method with a pre-experimental design, employing a one-group pre-test and post-test design. Both secondary and primary data were used, obtained from medical records and observation sheets. The research subjects were 40 pregnant women at Clinic GM Waras Bengkulu Utara, selected using a total sampling technique. Data analysis was conducted using the paired samples t-test. The results showed a difference in the mean hemoglobin levels of third trimester pregnant women before the intervention (10.363) and after the intervention (12.440). The administration of green spinach juice was found to be strongly associated with an increase in hemoglobin levels among third trimester pregnant women, with a p-value of 0.000 (< 0.005). The research site is expected to provide complementary care through the administration of green spinach juice to pregnant women as an alternative effort to prevent anemia during pregnancy, in addition to continuing the government’s program of providing Fe tablets once daily